From Classical Capitalism to Algorithmic Domination: The Rise of the Influence Industry - Hakim, Chairunisa S; Rajid, Julian Aldrin Pasha (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The emergence of digital capitalism has transformed economic, political, and social structures, shifting power from traditional industries to Big Tech monopolies that dominate global information flows. Unlike classical capitalism, which revolved around physical production and labor exploitation, digital capitalism thrives on data extraction, algorithmic governance, and predictive analytics. This transformation has led to the rise of the influence industry, a system where corporations, political actors, and state entities manipulate public opinion through microtargeted advertising, AI-driven misinformation, and algorithmic biases. As companies like Google, Meta (Facebook), and Amazon consolidate power, they exert unprecedented control over digital communication, influencing political discourse, electoral outcomes, and media narratives. This study critically examines the transition from classical to digital capitalism, analyzing how Influence Industry and Big Tech’s exacerbates economic inequality, distorts democratic processes, and facilitates the spread of misinformation. The research highlights key issues, including the Facebook–Cambridge Analytica scandal, AI-driven propaganda in geopolitical conflicts, and algorithmic amplification of extremist content. These developments underscore the urgent need for regulatory interventions to mitigate the risks posed by digital monopolies.